Erasmus+ 2021–2027 in higher education: Contributions to the 2030 agenda and to the Sustainable Development Goals - Nogueiro, T.; Saraiva, M.; Rolo, A. (Driving quality management and sustainability in VUCA environments: 4th International Conference on Quality Innovation and Sustainability (ICQIS), 2024)
The 2030 Agenda for Sustainable Development, approved by all UN member states in 2015, includes the 17 Sustainable Development Goals (SDGs), which are seen by Boeren (2019) as a Programme of actions not only for people but also for the planet and prosperity. These goals are essentially intended to help nations work together to build a cleaner world and a fairer global society while safeguarding the environment, and are aligned with those advocated by the Eras-mus+ Programme. Both the Programme and the SDGs have goals to be achieved and associated indicators that should be used as tools to achieve these goals that corroborate those outlined in the 2030 Agenda. This work aims to find out to which SDGs contribute most the Erasmus+ Programme. To this end, we used a qualitative analysis of the Regulation that led to the creation of the Erasmus+ Programme for the period 2021-2027 and the 17 SDGs. It was concluded that the most relevant SDGs are 4, 5, 8, 9, 10, 13, 16 and 17 and that the Erasmus+ Pro-gramme seems to have a strong potential to drive and mobilize Sustainable De-velopment in the world through the participation of people and the projects im-plemented and developed. It was also concluded that SDG 4 contributes directly or indirectly to the other selected SDGs, but no SDG contributes to SDG 4.